Estimasi Kemauan Masyarakat Membayar Biaya Lingkungan: Studi Kasus pada Kandang Kelompok Kambing Peranakan Etawah di Desa Girikerto, Turi, Sleman (Estimation of the People Willingness to Pay Environmental Cost: Case Study at Etawah Crossbreed Goat Group F - Tri Anggraeni Kusumastuti; Masyhuri (Masyhuri); Any Suryantini (Faculty of Animal Science, Universitas Gadjah Mada, 2009)
The aims of this study was to analyze the kind of people willingness to pay and the factors affecting the existence of Etawah crossbreed goat group farm. Girikerto Village, Turi, Sleman was chosen as research site because it was thecenter of Etawah crossbreed goat village system in Sleman. Samples of 40 people at surrounding area were determined purposively based on residence distance to the village group system location. To analyze the relation between the willingness to pay of people and its affecting factors Ordinal Logit Regression Analysis methods were used with STATA software version 6.0. Aid in labor form has higher value than material physical aid. It was due to in social institution role of social capital in form of voluntary work very much influent the existence of village group system. Model estimation with Ordinal Logit Regression, indicated that education, total income, distance of residence to village group system, salak plantation area, and occupation type had positively significant effect on people willingness to pay, while based on marginal effect calculation, all independent variables indicated negative tendency or low appreciation from people toward environment.(Key words: The willingness to pay of people, Ordinal Logit, Social capital, Marginal effect)